The Relevance of Biology Material to Indigenous Knowledge in the Bau nyale Tradition in Kute, Central Lombok - Hidayat, X Zardht Alex; Nanisfi, Maulidatin; Andayani, Yayuk; Japa, Lalu (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This study aims to identify and describe the biological aspects within the tradition of nyale scent through the indigenous knowledge of the community. The research utilizes a qualitative method with a phenomenological approach, focusing on collecting data regarding the nyale scent tradition. Data on indigenous knowledge were obtained through interviews with three sources: traditional leaders, village heads, and participants in the nyale scent tradition. The data were collected in narrative form and analyzed descriptively. The research findings indicate that the nyale scent tradition is relevant to biology, observed in various aspects such as the process of capturing nyale worms, the biology of nyale worms, and the utilization of nyale worms. Relevant biological topics associated with the nyale scent tradition include the classification of living organisms, ecosystems, reproduction, the human digestive system, and the structure and function of plants.